Gyártási folyamatok optimalizációja általános eloszlású időzített Petri háló szimulátorral - Molnár András (2016)
Nowadays, with the rapid development of technology, manufacturing systems are becoming more and more efficient. However, efficiency is often accompanied by the increase of system complexity. System complexity does not only appear in the number of system components but also in their diversity and the complexity of their relationships. System monitoring and analysis play a critical role in the maximization of productivity and in the optimization of the manufacturing processes. System analysis can be carried out by several tools, one of the most often used one is simulation. In my master thesis, I present TiPeNeSS (Timed Petri Net Simulator Software) which is an event-driven simulator for the evaluation of manufacturing systems. The goal of my work was to develop a simulation software which is able to represent the structure of a real (or planned) manufacturing system in a suitable model to measure the most important characteristics of it, as well as to support the system development process. The most important tasks during the analysis of manufacturing systems are the following: finding the bottleneck in the manufacturing system; measuring the average number of elements at the given workstations; measuring the effects of structural changes in the system; measuring the effects of failures in the system; measuring the effects of changes in the intervals of certain processes (for example increased demand); measuring the system productivity. Manufacturing systems are composed of vastly different elements that are in various kinds of relationship with each other. Thus, the occurring processes in the system are just as varied. The modeling of the occurring processes and events is no trivial task, free simulation software on the market like TimeNET [1] or GreatSPN [2] cannot or just partially can evaluate the mentioned systems. The simulation software uses Timed Petri Nets (TPNs) with generally distributed ﬁring times (e.g. normal, uniform or gamma distribution) as modeling tool. This tool allows the description of the manufacturing systems’ structure in detail, additionally it provides graphical representation for the system elements and their relationships. Furthermore, with the introduction of the memory policy option between transitions, the system processes and the effect of the occurring events can also be precisely described. With the introduction of a graphical user interface, the work with the simulator is much more user friendly, the graphical representation offered by the Petri net makes the structure transparent and easy to follow. The simulator guides the user along the whole analysis process, it supports the creation of the system model, the parameterization of the simulation, running the simulation, until the very end of the simulation process: the presentation of the results. The software is capable of running terminating and non-terminating simulations in addition to stability analysis. In this document, I summarize my work starting with a theoretical background, which covers the most important information about probability theory, statistics and simulation from my work point of view. After covering the theory, I present the structure of the simulator and guide the reader through the design process, dedicating a separate chapter for the graphical user interface, followed by the detailed description of the updating process of the event queue. Then, I demonstrate the strengths of the simulator with the help of a case study. Finally, I complete my work with a summary and listing ideas for future development.